Diglossia: Keep preserving High and Low Language of Javanese varieties - Jumharia Djamereng (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
The research intends to describe the use of diglossia among Javanese societies who are settling in Sukamaju Sub district North Luwu Regency.  Diglossia is formed as a functional of language variety which is used by communities in interaction among others. In a speech community, people may bilingual and multilinguals, thus one language usually has standard and non-standard language. Standardized language or High variety is generally used in formal situation while non-standard language mostly used in daily interaction or informal situation. The research was designed in descriptive qualitative method as it intends to describe how Javanese people choose the High variety and Low variety when communicating with their family and fellows based on the situation. The instrument of the research was observation to gather data related to language use that were spoken by Javanese people in daily interaction. Interview was used to gather information related to the use of diglossia of Javanese language among Javanese people. The informants were 40 Javanese people that  comprises 4 age groups; > 60 years old, 30-59 years old, 13-29 years old, and <12 years old. The research found there are still sustainable use of diglossia among Javanese societies who are living in Sukamaju Sub district, Noth Luwu Regency. The pattern of diglossia follows “bilingual with diglossia” because they are multilingual (Javanese language, local language “Tae language”, Indonesian language) and also use functionally the High and Low varieties of  Javanese language. The low variety are mostly used in all age groups in daily interaction. The <12 age group do not totally understand High variety, but they still use the Low variety of Javanese when communicating with friends and family.